2021
DOI: 10.1007/s40789-021-00460-2
|View full text |Cite
|
Sign up to set email alerts
|

Stress and deformation analysis of gob-side pre-backfill driving procedure of longwall mining: a case study

Abstract: At present, non-pillar entry protection in longwall mining is mainly achieved through either the gob-side entry retaining (GER) procedure or the gob-side entry driving (GED) procedure. The GER procedure leads to difficulties in maintaining the roadway in mining both the previous and current panels. A narrow coal pillar about 5–7 m must be left in the GED procedure; therefore, it causes permanent loss of some coal. The gob-side pre-backfill driving (GPD) procedure effectively removes the wasting of coal resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…During testing, AE signals were recorded simultaneously with the cracking process [54]. During loading, Liu et al and Zhu et al have made the effort to investigate the AE signal frequency features with both saturated and dry coals, and the outcomes revealed that the AE signals with a high frequency were pointedly reduced by water content [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…During testing, AE signals were recorded simultaneously with the cracking process [54]. During loading, Liu et al and Zhu et al have made the effort to investigate the AE signal frequency features with both saturated and dry coals, and the outcomes revealed that the AE signals with a high frequency were pointedly reduced by water content [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation overcomes the limitation of laboratory size and can well analyze the stability of rock mass under complex geological conditions [10][11][12]. Compared with experiments, numerical simulation can quantitatively control the properties and quantities of particles or elements, and numerical simulation is widely used to analyze large-scale engineering problems [13,14]. However, it is still tricky to correctly reproduce the spatial mechanical response of the stope in the numerical simulation of finite element and finite difference methods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found, that when the rock breaks, it usually releases electromagnetic energy [26][27][28][29][30][31], elastic energy [32][33][34][35][36][37][38][39][40][41], thermal energy [42][43][44], acoustic energy [45][46][47][48][49][50][51], and other kinds of energy [52]. Hence, generating a variety of disaster warning methods related to rock mass, such as infrared radiation method [53,54], electromagnetic radiation method [55,56], acoustic emission method [57,58], potential method [51,59] and microseismic method [60,61]. Among these, as a non-contact method, the infrared radiation method has the advantages of high accuracy [62], strong reliability [63], simple operation [64], and visualization [65], etc., which provides a convenient and accurate early warning method for rock fracture seepage monitoring under coupled stress-hydro effect.…”
Section: Introductionmentioning
confidence: 99%